Neurexin and Neuroligins Maintain the Balance of Ghost and Satellite Boutons at the Drosophila Neuromuscular Junction - Gan Guangming; Gan Guangming; Geng Junhua; Zhang Chenchen; Zhang Chenchen; Mou Yang; Xie Wei; Xie Wei (Frontiers Media S.A., 2020)
Neurexins and neuroligins are common synaptic adhesion molecules that are associated with autism and interact with each other in the synaptic cleft. The Drosophila neuromuscular junction (NMJ) bouton is a well-known model system in neuroscience, and ghost and satellite boutons, respectively, indicate the poor development and overgrowth of the NMJ boutons. However, the Drosophila neurexin (DNrx) and Drosophila neuroligins (DNlgs) are mainly observed in type Ib boutons, indicating the ultrastructural and developmental phenotypes of the Drosophila NMJ. Here, we identified the ultrastructural and developmental features of ghost and satellite boutons by utilizing dneurexin (dnrx) and dneuroligins (dnlgs) fly mutants and other associated fly strains. Ghost boutons contain synaptic vesicles with multiple diameters but very rarely contain T-bar structures and swollen or thin subsynaptic reticulum (SSR) membranes. The muscle cell membrane is invaginated at different sites, stretches to the ghost bouton from different directions, forms several layers that enwrap the ghost bouton, and then branches into the complex SSR. Satellite boutons share a common SSR membrane and present either a typical profile in which a main bouton is encircled by small boutons or two atypical profiles in which the small boutons are grouped together or distributed in beads without a main bouton. Electron and confocal microscopy data showed that dnrx, dnlg1, dnlg2, dnlg3, and dnlg4 mutations led to ghost boutons; the overexpression of dnrx, dnlg1, dnlg2, dnlg3, and dnlg4 led to satellite boutons; and the dnlg2;dnlg3 double mutation also led to satellite boutons. These results suggested that DNrx and DNlgs jointly maintain the development and function of NMJ boutons by regulating the balance of ghost and satellite boutons in Drosophila.